Novel Cycloheximide Derivatives Targeting the Moonlighting Protein Mip Exhibit Specific Antimicrobial Activity Against Legionella pneumophila - Rasch, Janine; Theuerkorn, Martin; Ünal, Can; Heinsohn, Natascha; Tran, Stefan; Fischer, Gunter; Weiwad, Matthias; Steinert, Michael (Frontiers in Bioengineering and Biotechnology, 2015)
Macrophage infectivity potentiator (Mip) and Mip-like proteins are virulence factors in a wide range of pathogens including Legionella pneumophila. These proteins belong to the FK506 binding protein (FKBP) family of peptidyl-prolyl-cis/trans-isomerases (PPIases). In L. pneumophila, the PPIase activity of Mip is required for invasion of macrophages, transmigration through an in vitro lung–epithelial barrier, and full virulence in the guinea pig infection model. Additionally, Mip is a moonlighting protein that binds to collagen IV in the extracellular matrix. Here, we describe the development and synthesis of cycloheximide derivatives with adamantyl moieties as novel FKBP ligands, and analyze their effect on the viability of L. pneumophila and other bacteria. All compounds efficiently inhibited PPIase activity of the prototypic human FKBP12 as well as Mip with IC50-values as low as 180 nM and 1.7 μM, respectively. Five of these derivatives inhibited the growth of L. pneumophila at concentrations of 30–40 μM, but exhibited no effect on other tested bacterial species indicating a specific spectrum of antibacterial activity. The derivatives carrying a 3,5-dimethyladamantan-1-[yl]acetamide substitution (MT_30.32), and a 3-ethyladamantan-1-[yl]acetamide substitution (MT_30.51) had the strongest effects in PPIase- and liquid growth assays. MT_30.32 and MT_30.51 were also inhibitory in macrophage infection studies without being cytotoxic. Accordingly, by applying a combinatorial approach, we were able to generate novel, hybrid inhibitors consisting of cycloheximide and adamantane, two known FKBP inhibitors that interact with different parts of the PPIase domain, respectively. Interestingly, despite the proven Mip-inhibitory activity, the viability of a Mip-deficient strain was affected to the same degree as its wild type. Hence, we also propose that cycloheximide derivatives with adamantyl moieties are potent PPIase inhibitors with multiple targets in L. pneumophila.